Free radicals, reactive oxygen species, oxidative stresses and their classifications - V. I. Lushchak (The Ukrainian Biochemical Journal, 2015)
The phrases “free radicals” and “reactive oxygen species” (ROS) are frequently used interchangeably although this is not always correct. This article gives a brief description of two mentioned oxygen forms. During the first two-three decades after ROS discovery in biological systems (1950-1970 years) they were considered only as damaging agents, but later their involvement in organism protection and regulation of the expression of certain genes was found. The physiological state of increased steady-state ROS level along with certain physiological effects has been called oxidative stress. This paper describes ROS homeostasis and provides several classifications of oxidative stresses. The latter are based on time-course and intensity principles. Therefore distinguishing between acute and chronic stresses on the basis of the dynamics, and the basal oxidative stress, low intensity oxidative stress, strong oxidative stress, and finally a very strong oxidative stress based on the intensity of the action of the inductor of the stress are described. Potential areas of research include the development of this field with complex classification of oxidative stresses, an accurate identification of cellular targets of ROS action, determination of intracellular spatial and temporal distribution of ROS and their effects, deciphering the molecular mechanisms responsible for cell response to ROS attacks, and their participation in the normal cellular functions, i.e. cellular homeostasis and its regulation.